2004
DOI: 10.1111/j.1048-891x.2004.14414.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent primary vulvovaginal malignant melanoma arising in melanoma in situ- the natural history of lesions followed for 23 years

Abstract: Multifocal melanoma and melanoma in situ of the vulva and vagina are uncommon lesions, and our understanding of their natural history is limited. Vulvovaginal melanoma appears to be biologically different from cutaneous melanoma and has more in common with mucosal melanoma. A 60-year-old woman presented in 1977 with a pigmented vulvar lesion. Histologic examination revealed melanoma in situ associated with focal invasive melanoma. She re-presented with recurrent primary melanomas arising in melanoma in situ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Although typically confined to case series and single-institution studies, data regarding the treatment and survival outcomes of patients with mucosal melanoma of the LGT illustrate a difficult-to-control disease with poor outcomes in all stages ( Brand et al, 1989 , Leitao et al, 2014 , DeMatos et al, 1998b , Harting and Kim, 2004 , Kingston et al, 2004 , Bennani et al, 2013 ). Historically, 5-year survival rates for patients with vaginal melanoma have been calculated to be as low as 5–10% ( Harting and Kim, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although typically confined to case series and single-institution studies, data regarding the treatment and survival outcomes of patients with mucosal melanoma of the LGT illustrate a difficult-to-control disease with poor outcomes in all stages ( Brand et al, 1989 , Leitao et al, 2014 , DeMatos et al, 1998b , Harting and Kim, 2004 , Kingston et al, 2004 , Bennani et al, 2013 ). Historically, 5-year survival rates for patients with vaginal melanoma have been calculated to be as low as 5–10% ( Harting and Kim, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our cohort, all male patients with an initial truncal BCC developed a further BCC within 3AE5 years. 4 Moreover, we have recently shown that first presentation with a truncal tumour is associated with significantly more subsequent BCCs on this site compared with patients with an initial lesion on the head or neck. 5 In contrast, the rate of increase of nontruncal BCCs per year was similar in patients with and without initial truncal lesions, suggesting that different mechanisms determine the development of truncal and nontruncal BCC.…”
Section: Conflicts Of Interest: None Declaredmentioning
confidence: 91%
“…2,3 Treatment is usually surgical, with some advocating the radical approach of a vulvovaginectomy, because of the likely field change and because of the poor prognosis associated with invasive disease (5-year survival of 47%). 4 Imiquimod 5% cream is a topical immunomodulator that has been used successfully to treat a number of skin cancers, including in situ 5 and metastatic melanoma. 6 We report a 68year-old woman with multifocal melanoma in situ of the vulva successfully treated with 4 months of topical imiquimod.…”
mentioning
confidence: 99%
“…Destruction by cryosurgery, cautery or laser is contraindicated, and all such lesions must undergo histopathological evaluation. Small lesions often can be completely excised, and when sampling hyperpigmented areas, a biopsy of the thickest region is recommended (138, 141). If the diagnosis is considered within the differential diagnosis of pigmented vulvar lesions, it is easy to recognize and treat, with excellent prognosis (142).…”
Section: Melanoma In Situ Of the Vulvamentioning
confidence: 99%
“…Melanoma in situ (MIS) is rare on the vulva and appears to have a relatively slow but definite progression to invasive melanoma (138). The ABCDE scheme for recognition of melanoma should be considered in pigmented lesions ( A symmetry, B order irregularities, C olor variation, D iameter > 6mm, E nlargement or E volution of color change, shape or symptoms) (139, 140).…”
Section: Melanoma In Situ Of the Vulvamentioning
confidence: 99%